Dampak Gig Economy terhadap Kinerja Sosial dan Lingkungan pada Sektor Transportasi Daring: Perbandingan Perspektif Perusahaan Platform dan Mitra Driver - Yoga, Ibnu Abi; Maarif, Mohamad Syamsul; I Made Sumertajaya (Jurnal Ilmiah Global Education, 2025)
This study aims to analyze the impact of the gig economy on social and environmental performance in the online transportation platform sector in the Greater Jakarta area by comparing the perspectives of platform companies and gig workers (driver partners). This study uses a case study design with a mixed method combining Likert scale questionnaires and in-depth interviews. The respondents consist of 183 platform company employees and 101 driver partners from various online transportation companies. Data analysis was conducted using descriptive statistical approaches and Structural Equation Modeling–Partial Least Squares (SEM–PLS). The results indicate that the gig economy significantly impacts social and environmental performance from both perspectives, though with differing levels of perception. Driver partners tend to experience stronger positive impacts regarding work flexibility, income opportunities, and involvement in environmental efforts, yet they still face challenges such as income instability, limited job protection, and unequal access to social programs. Platform companies acknowledge the gig economy's contribution to social and environmental aspects, though with a more moderate assessment. These findings underscore the importance of integrating social and environmental dimensions into core business strategies, as well as the need to incorporate driver partners' input to strengthen the sustainability and inclusivity of the gig economy ecosystem in the future.